Morphological changes in blood in pneumonia in children, taking into account the impact of COVID-19 - Dutchuk, Oksana; Kocherha, Zoryana (ScienceRise: Medical Science, 2025)
The study of morphological changes in blood in pneumonia in children, in particular those accompanied by coronavirus infection, is an important aspect for improving diagnostics and predicting the occurrence of complications arising from the action of oxidative stress. Objective: to identify and compare morphological changes in blood in children with pneumonia depending on the presence of COVID-19 infection, to find out which morphological indicators are associated with the severity of the disease and to assess the significance of morphological markers for the development of complications. Materials and methods: A cohort study was conducted on the basis of the pulmonology department of the Ivano-Frankivsk Regional Children's Clinical Hospital of the Ivano-Frankivsk Regional Council in the period 2021-2025. Children aged 1-3 years with clinical and radiological confirmation of pneumonia were included. For this study, 60 young children (1-3 years old) diagnosed with community-acquired pneumonia were selected and divided into 2 groups according to the presence of complicated pneumonia. Results: Using ultrastructural blood analysis, it was found that the most pronounced morphological changes are observed in complicated cases of COVID-19. Erythrocytes change their shape, some of them are destroyed, others participate in the formation of microthrombi. Among leukocytes, an increase in the number of segmented neutrophils, lymphocytes and monocytes is noted. Conclusions. The results of the study will clarify the prognostic role of morphological changes in the blood in children with pneumonia, in particular with concomitant COVID-19 infection